10 Year Outcome Following Meniscus Repair Using Inside-Out Technique: A Comparative Cohort of Patients 40 years and Older vs Patients Younger than 40. Issue 7 (29th July 2014) - Steadman, J. Richard; Crespo, Bernardo; Johnson, Nicholas; Matheny, Lauren; Briggs, Karen K.
Objectives: The number of meniscus repairs being performed is increasing, as research supports the need to preserve native meniscus tissue. Although excellent short-term results have been published after meniscus repair, there are limited data available on longer outcomes in patients treated with a single type of repair. The purpose of this study was to compare failure rate and clinical outcomes 10 years following mensicus repair, using inside-out technique, by a single surgeon in patients 40 years and older and patients younger than 40 years. Methods: A prospective data registry was queried for knee arthroscopies between 1992 and 2003 for meniscus repairs performed by a single surgeon. This study was IRB approved. Patients who underwent arthroscopic meniscus repair using inside-out technique were included. Exclusion criteria included patients younger than 18 years. Repairs were considered a failure if the knee had a subsequent surgery on the same meniscus or the knee was converted to a total knee arthroplasty(TKA). If knees required subsequent surgery on the meniscus, it was documented if it was a re-repair or meniscectomy. General health measure included the SF12 physical component score (PCS) and the mental component score(MCS). Condition specific outcomes included the Lysholm score, WOMAC and IKDC score. Activity was measured by the Tegner activity scale and patient satisfaction with outcome was measure on a 1 to 10 scale with 10 being very satisfied. Outcomes and failures were compared between patients 40 years and older(40P) and patients younger than 40(40Y). Results: 206 patients were met the inclusion criteria. The average age was 33 years (range, 18 to 70 years) and there were 75 females and 131 males. Sixty-four (31%) knees underwent a subsequent knee surgery; 61 patients had a second meniscus surgery on the same meniscus and three had a TKA, and were therefore considered failures. Of the 61 patients who underwent a second meniscus surgery, 47 had a meniscectomy and 14 had a meniscus repair. The average age of the failure group was 33 years (range, 18 to 65 years), with 15 over the age of 40 at time of repair. The was no difference in the number of failures between 40P group and 40Y group(p=0.975) The average time to failure was 4.9 years postoperatively (range, 0.8 months to 18.6 years). Of the remaining patients, average followup was 14 years (range, 10 to 21 years). The average PCS was 54 and the average MCS was 54. The average Lysholm at latest followup was 86, the average WOMAC was 6 and the average IKDC was 73. The median Tegner activity scale was 6 (range, 1 to 9). The median patient satisfaction with outcome was 9 (range, 1 to 10). There was no difference in any outcome measure between the 40P group and the 40Y group. Conclusion: Ten years following meniscus repair, 30% of patients required repeat surgery of the meniscus or had a TKA. Older patients did not experience increased failures. Outcomes showed excellent function, low disability and high activity level 10 years following meniscus repair.